A Randomized, Placebo-Controlled Trial Evaluating Changes in Peripheral Neuropathy and Quality of Life by Using Low-Frequency Electrostimulation on Breast Cancer Patients Treated With Chemotherapy. (June 2020) - Song, Si-Yeon; Park, Ji-Hye; Lee, Jin Sun; Kim, Je Ryong; Sohn, Eun Hee; Jung, Mi Sook; Yoo, Hwa-Seung
Background: This study examined the effect of a portable low-frequency electrostimulation (ES) device on patients diagnosed with chemotherapy-induced peripheral neuropathy (CIPN) immediately after chemotherapy for breast cancer.Methods: A single-center, randomized, placebo-controlled trial was conducted. A total of 72 patients newly diagnosed with CIPN were enrolled and randomly placed into the ES (n = 36) or the sham ES group (SES; n = 36). Duloxetine or pregabalin was prescribed to all participants from the initial assessment. The devices for 14 days, at least twice a day, for at least 120 minutes. The primary outcomes were the overall intensities of the CIPN symptoms as assessed using Numerical Rating Scale (NRS). Secondary outcomes included Total Neuropathy Score (TNS), European Organization for Research and Treatment of Cancer Quality of Life (EORTC-QLQ), Chemotherapy-Induced Peripheral Neuropathy 20 (CIPN20), Functional Assessment of Cancer Therapy-Breast (FACT-B), and Instrument on Pattern Identification and Evaluation for CIPN (IPIE-CIPN).Results: No differences in NRS scores were found between the patients in the ES and the SES group ( P = 0.267). Patients in both groups showed significantly reduced CIPN intensities (ES P < .001; SES P < .001). No significant differences between the groups were found in TNS, EORTC-QLQ, CIPN20, and FACT-B. The general symptoms of CIPN diagnosed as cold arthralgia showed significance only in the ES group ( P = .006).Conclusion: Compared with a placebo, the effectiveness of the low-frequency ES device with pharmacological intervention was not significantly different, but a therapeutic effect was possible.